The Impact of Various Mode of Financings in Reducing Inequality in Various Groups of Countries - Irma Yuliani; Muhammad Abdul Rohman (Journal of Finance and Islamic Banking, 2020)
The existence of Islamic bank not always provide positive impact to the real sector of economy. Declining inequality is one of the expected significant impacts with appyling mode of financing as instrument to relize that. This study aims to investigate the impact of mode of financing was applied by Islamic bank to reduce inequality among countries of IsDB Group. World bank data and IDB data of Islamic banks are employed as samples from 1977 to 2018. The results show that equity and leasing have a positive effect and significant to reduce inequality for low income countries, where the leasing or ijarah have the most effective impact than all. In addition, instalment sale of financing has a significant impact to reduce inequality for middle-income countries, loan is being the only significant mode of financing to reduce inequality in all IDB countries. Unfortunately, Mudharabah, PLS (profit and loss sharing), Murabahan and Istishna have not significantly impact to reduce inequality